Retroperitoneal myofibroblastoma in an 88‐year‐old male. Issue 5 (14th June 2022) - Watari, Shogo; Ichikawa, Takaharu; Shiraishi, Hiromasa; Sakuma, Takafumi; Kubota, Risa; Kusumi, Norihiro; Tsushima, Tomoyasu; Nagakita, Keina; Shinno, Yoko
Abstract : Introduction: Extramammary myofibroblastomas are extremely rare. Case presentation: The patient was an 88‐year‐old male. He presented for evaluation of frequent urination and a "pushing up" sensation from the groin during defecation. Thorough physical and radiographic examinations revealed a retroperitoneal tumor on the right side of the rectum. The pathologic examination of the biopsy tissue showed that the tumor was unlikely to be malignant. Nevertheless, the patient was symptomatic and thus underwent a laparoscopic tumor resection through a transperitoneal approach. The tumor was circumscribed with a solid capsule. Based on the pathologic findings, which included immunostaining, the tumor was diagnosed as a myofibroblastoma. There was no evidence of a recurrence 6 months postoperatively. Conclusion: We present this case with the clinical course and surgical findings, and discuss the possibility of establishing a preoperative pathologic diagnosis of a myofibroblastoma.